Mothering behind bars: The policy on pregnant inmates and the custody of their newborn - Cantimbuhan, Mariane Philine T. (Animo Repository, 2020)
The sad reality is, not all children are born to completely capacitated mothers who are without any legal impediment or hindrances to take care of them. There are some who are born to state offenders, or whose mothers committed a wrong against the state and as a consequence of which, the mother has to serve sentence inside a penitentiary or prison. When such is the situation, the pressing issue is whether or not an incarcerated pregnant is allowed to “mother” or “parent” her newborn after she had given birth. Countries without prison nurseries, like the Philippines, consequently forces incarcerated mothers and their newborn to be separated at birth. Although it is not a normal to raise a child in prison, it does not mean that such option has to be completely disregarded, especially when it tends to the best interest of the child. It is true that mothers may not be the only one left to provide love and care for the newborn, but incarcerated mothers should be given options on what to do with their newborn. This paper aims to contribute to the literature involving the rising population of pregnant inmates in the country. Furthermore, it calls for government’s action and response to provide effective health care services and facilities that will cater to the needs of pregnant women in prison and to their newborn babies pursuant to the fundamental rights enshrined in the 1987 Philippine Constitution such as protection of the life of the mother and the unborn, and under the UN Conventions which affords special protection to mothers before, during and after childbirth.